The impact of optimally dispatched energy storage devices on electricity price volatility. (May 2022) - Hu, Tingli; Wang, Caisheng
Abstract: A high level of electricity price volatility increases financial risks and safety issues in power system operations. Storage devices as an efficient solution to mitigating price volatility have attracted extensive attention. In this paper, the mechanism of how storage devices impact price volatility is investigated at first. Through analyzing the connection between an economic dispatch problem and its Lagrange dual, we reveal that the capacity and charge/discharge power of a storage device installed at a node have an aggregate impact on the range of the price changes of that node. A model to calculate the sensitivity of price volatility to storage device parameters is proposed. To determine the optimal nodes to place storage devices and the optimal storage capacities to constrain the price change levels, this paper develops a chance-constrained optimization model, and a scenario-based approach is adopted to solve the problem. The IEEE 24-bus system is employed in the case studies, associated with Gurobi and Julia. Simulation studies show that if there is one node with the highest price change all the time, the price volatility must have the highest sensitivity to the storage device on that node. However, in the case where there are multiple nodes having the highest price changes at different times, a node with high price change does not necessarily mean high sensitivity. The simulation studies verify that the chance-constrained optimization model is effective to suppress excess price changes. Highlights: The impact of energy storage devices on price volatility is revealed by Lagrange duality. A model to calculate sensitivity of price volatility to storage parameters is established. A chance-constrained optimization model is proposed to find the optimal nodes to place storage devices.